Regulating electronic properties of BiOBr to enhance visible light response via 3d transition metals doping: DFT + U calculations. Issue 7 (30th November 2020) - Guan, Meihua; Ren, Guangmin; Zhang, Xiaochao; Zhang, Qirui; Zhang, Changming; Li, Rui; Fan, Caimei
Abstract: In our work, the formation energies, band structures, densities of states, effective masses and optical absorption properties of pure BiOBr and 3d transition metals‐doped BiOBr have been calculated using DFT + U method. Ti, V, Fe, Cr, Co, Ni and Cu doping can induce impurity energy levels, originating from spin‐up or ‐down orbits of 3d transition metals (TMs), within the forbidden band of BiOBr, but Sc, Mn and Zn atoms only change the electronic delocalization in the valence band or conduction band region of BiOBr. Furthermore, with introduction of 3d TMs atoms, there exist the redshift phenomena for optical absorption band edge of BiOBr to different extents. The photo response priority order, structural stability and recombination probability of photoinduced carriers for 3d TMs‐doped BiOBr are summarized. Our theoretical findings should well explain the experimental observations in the previous literatures, and provide promising prediction and significant guidance for the well‐construction of BiOBr‐based photocatalyst systems. Abstract : DFT + U calculations on regulating the electronic structures through 3d transition metals (TMs = Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn) doping to enhance the visible light response. The priority orders of 3d TMs‐doped BiOBr systems in light response, structural stability and inhibit charge carrier recombination of pure and 3d TMs‐doped BiOBr systems are summarized.